2020
DOI: 10.1177/1524838020916254
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Barriers to Formal Help Seeking for Adult Survivors of IPV in the United States, 2005–2019

Abstract: For individuals experiencing intimate partner violence (IPV), formal services, including community agencies, health services, or the criminal justice system, are critical resources. Understanding the specific barriers that hinder or prevent survivors from seeking help from formal services could reveal important implications for the development of services for IPV as well as for members of other organizations who encounter survivors. The authors conducted a systematic review of the literature to identify barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
100
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(120 citation statements)
references
References 54 publications
11
100
1
1
Order By: Relevance
“…Although there is well-known evidence concerning the barriers that IPVAW victims face when weighing the decision to disclose the violence they have experienced [ 58 ], the psychosocial characteristics—at different levels of social ecology—that affect public decisions to provide help remain unclear [ 33 ]. To clarify this gap, we analyzed differences in individuals’ helping reactions to known IPVAW victims across 28 European countries by examining whether (a) at the individual level, gender-related attitudes and perceptions toward different forms of VAW would replicate prior effects with real self-reported help, and (b) at the country level, gender-related macrosocial ideological and structural characteristics would promote helping reactions to known IPVAW.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is well-known evidence concerning the barriers that IPVAW victims face when weighing the decision to disclose the violence they have experienced [ 58 ], the psychosocial characteristics—at different levels of social ecology—that affect public decisions to provide help remain unclear [ 33 ]. To clarify this gap, we analyzed differences in individuals’ helping reactions to known IPVAW victims across 28 European countries by examining whether (a) at the individual level, gender-related attitudes and perceptions toward different forms of VAW would replicate prior effects with real self-reported help, and (b) at the country level, gender-related macrosocial ideological and structural characteristics would promote helping reactions to known IPVAW.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies showed changes in police calls for DV service during COVID‐19, prior research has consistently demonstrated that most DV victims do not call police after incidents of violence (Morgan & Truman, 2020 ). Victims of DV describe a range of barriers to reporting to police, including concerns that they will not be believed or that nothing will be done, fears of retaliation by the perpetrator, and a reliance on the perpetrator for material resources (e.g., housing and financial support), among others (Robinson et al., 2020 ). The pandemic‐related economic downturn has likely increased concerns regarding negative consequences of reporting to police, and victims may be inclined to access support and resources from other sources such as emergency hotlines (Sorenson et al., 2021 ).…”
mentioning
confidence: 99%
“…While these studies showed changes in police calls for DV service during COVID-19, prior research has consistently demonstrated that most DV victims do not call police after incidents of partner violence (Morgan & Truman, 2020). Victims of DV describe a range of barriers to reporting to police, including concerns that they will not be believed or that nothing will be done, fears of retaliation by the perpetrator, and a reliance on the perpetrator for material resources (e.g., housing, financial support), among others (Robinson, Ravi, & Voth Schrag, 2020). The pandemic-related economic downturn has likely increased concerns regarding negative consequences of reporting to police, and victims may be inclined to access support and resources from other sources like emergency hotlines (Sorenson, Sinko, & Berk, 2021).…”
Section: Comparing 911 and Emergency Hotline Calls For Domestic Violence In Seven Cities: What Happened When People Started Staying Home mentioning
confidence: 99%